Log Event Management Server Menggunakan Elastic Search Logstash Kibana (ELK Stack) - Walidatush Sholihah; Sangga Pripambudi; Anggi Mardiyono (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
This study aims to build an Event Management Server Log using ELK Stack (Elastic searchLogstash Kibana) which can make it easier to read and analyze log services on the server. TheEvent Management Server log in this study uses CentOS 7 as the Central Server and CentOS7 as a client-server with ssh services installed. This research consists of five stages. The stagesare analysis, network design, server configuration, client configuration, and testing. Theexperimental results show that all ssh log services that occur on the client-server sent inrealtime to the central server. Even though the contents of the log file on the client-server hasdeleted. In This study, in addition to sending logs, it can also display a percentage of successreferences.